Genetic diversity of Apis mellifera filamentous virus in bees sampled in the USA and Jamaica - Rohan A. Bandoo; Simona Kraberger; Cahit Ozturk; Qiyun Zhu; Brian Smith; Mart Krupovic; Chelsea Cook; Arvind Varsani (Archives of Virology, 2026)

Investigating the effects of biogenic amines on the dominance hierarchy in the small carpenter bee, Ceratina calcarata - Riya N. Miller; Sandra M. Rehan; Chelsea N. Cook; Colin S. Brent; Sarah P. Lawson (Insectes Sociaux, 2026)
Biogenic amines are highly conserved across animal species and aid in the regulation of movement, behavior, motivation, temperature, blood pressure, and endocrine secretion. Within eusocial species, such as the honey bee Apis mellifera , biogenic amines are responsible for modulating traits associated with higher levels of sociality, such as division of labor. In Ceratina calcarata , a facultatively social bee species, mothers establish a dominance hierarchy over their eldest daughter by providing them with less pollen and less protein, resulting in smaller, more submissive adults referred to as dwarf eldest daughters (DEDs). We hypothesized that this dominance hierarchy is additionally modulated by biogenic amines. To examine this hypothesis, we first compared biogenic amine levels between mothers and daughters and found significantly higher levels of dopamine, octopamine and tyramine in the mothers. To quantify the effects of these biogenic amine differences, dopamine was topically administered to C. calcarata DEDs, while the mothers were topically treated with the dopamine blocker cis-(Z)-Flupentixol dihydrochloride. Aggression helps to establish social hierarchies, so mothers and DEDs from the same nest underwent behavioral assays to assess aggressive and tolerant behaviors. When dopamine was blocked in the naturally more aggressive mothers, there was no difference in the number of aggressive interactions. Instead, treated mothers became more tolerant of DEDs, indicating dopamine plays a key role in modulating these behaviors. More work is needed to understand the different roles each biogenic amine plays in the development of a dominance hierarchy, especially in these species on the brink of eusociality.

Soil organic carbon better described by soil mineralogy and exchangeable cations than oak restoration in California rangelands - Stewart G. Wilson; Erika J. Foster; Fiona O’Neill; Ashely Banuelos; Avalon Cook; Keith Paustain; Yamina Pressler; Chelsea J. Carey (CATENA, 2025)

The Properties of Individual Fire Events Are Essential for Understanding Global Fire Regimes - Adam L. Mahood; Ty Tuff; Megan E. Cattau; Virginia Iglesias; Thomas E. Hanson; Jilmarie Stephens; Nayani Ilangakoon; Maxwell C. Cook; R. Chelsea Nagy; David Barnard; E. Natasha Stavros; Amy DeCastro; et al. (Global Ecology and Biogeography, 2025)
Aim As fire activity changes globally, we need to better understand the spatial and temporal characteristics of the individual events that, when aggregated, constitute fire regimes. Most global studies analyze point detections of burned area, without delineating or considering the properties of individual events. Furthermore, there is a critical need to understand fire patterns within the context of the geopolitical boundaries within which fires are managed. Location Global. Time Period 2003–2020. Major Taxa Studied Fire. Methods We divided 241 countries by Köppen‐Geiger climate classifications and quantified four event‐based fire regime metrics: size, duration, and mean and maximum growth rate; and four area‐based metrics: burned area, number of fires, season length, and season peak. We examined the correlations among fire regime components, and between each fire regime component and climate normals. We quantified temporal trends, and used mixed models to analyze how climate and landcover change were associated with event‐based components of fire regimes. Results Event‐based metrics were weakly correlated with area‐based metrics. Countries with warmer and less variable climates had high burned area, more fire events, longer season lengths and shorter event durations. Countries with high annual temperature range and low precipitation tended to have fewer events but larger fires that were faster‐spreading and occurred later in the year. The growth rate and size of individual fire events are increasing in 18% and 21% of regions we analysed, respectively. Interannual variability in size and growth rate was associated with aridity increases in boreal areas, and landcover changes in arid areas. Main Conclusions Drivers of burned area and fire seasonality are well understood but largely unrelated to the properties of individual events. A more detailed understanding of the spatial and temporal aspects of fire events at broad scales will assist fire management efforts in preparing for a warmer future.

The influence of complex matrices on method performance in extracting and monitoring for microplastics - Leah M. Thornton Hampton; Hannah De Frond; Kristine Gesulga; Syd Kotar; Wenjian Lao; Cindy Matuch; Stephen B. Weisberg; Charles S. Wong; Susanne Brander; Silke Christansen; Cayla R. Cook; Fangni Du; et al. (Chemosphere, 2023)

Early olfactory, but not gustatory processing, is affected by the selection of heritable cognitive phenotypes in honey bee - Meghan M. Bennett; Chelsea N. Cook; Brian H. Smith; Hong Lei (Journal of Comparative Physiology A, 2021)